Transcriptome analysis in switchgrass discloses ecotype difference in photosynthetic efficiency - Serba, Desalegn D.; Uppalapati, S. R.; Krom, N.; Mukherjee, S.; Tang, Y. H.; Mysore, K. S.; Saha, M. C. (My University, 2017)
Background: Switchgrass, a warm-season perennial grass studied as a potential dedicated biofuel feedstock, is classified into two main taxa - lowland and upland ecotypes - that differ in morphology and habitat of adaptation. But there is limited information on their inherent molecular variations. Results: Transcriptome analysis by RNA-sequencing (RNA-Seq) was conducted for lowland and upland ecotypes to document their gene expression variations. Mapping of transcriptome to the reference genome (Panicum virgatum v1. 1) revealed that the lowland and upland ecotypes differ substantially in sets of genes transcribed as well as levels of expression. Differential gene expression analysis exhibited that transcripts related to photosynthesis efficiency and development and photosystem reaction center subunits were upregulated in lowlands compared to upland genotype. On the other hand, catalase isozymes, helix-loop-helix, late embryogenesis abundant group I, photosulfokinases, and S-adenosyl methionine synthase gene transcripts were upregulated in the upland compared to the lowlands. At >= 100x coverage and >= 5% minor allele frequency, a total of 25,894 and 16,979 single nucleotide polymorphism (SNP) markers were discovered for VS16 (upland ecotype) and K5 (lowland ecotype) against the reference genome. The allele combination of the SNPs revealed that the transition mutations are more prevalent than the transversion mutations. Conclusions: The gene ontology (GO) analysis of the transcriptome indicated lowland ecotype had significantly higher representation for cellular components associated with photosynthesis machinery controlling carbon fixation. In addition, using the transcriptome data, SNP markers were detected, which were distributed throughout the genome. The differentially expressed genes and SNP markers detected in this study would be useful resources for traits mapping and gene transfer across ecotypes in switchgrass breeding for increased biomass yield for biofuel conversion.
Citation: Serba, D. D., Uppalapati, S. R., Krom, N., Mukherjee, S., Tang, Y. H., Mysore, K. S., & Saha, M. C. (2016). Transcriptome analysis in switchgrass discloses ecotype difference in photosynthetic efficiency. Bmc Genomics, 17, 14. doi:10.1186/s12864-016-3377-8
Keywords: Switchgrass; Transcriptome; Ecotype; Photosynthesis; Snp Markers; Panicum-Virgatum L.